Pengaruh Efektivitas Pesan CSR melalui Instagram terhadap Pembentukan Citra lia s. Associates Branding dan Design Agency - Salsabila, Annisa; Sudaryanto, Edy; Rizqi, Muchammad; Romadhan, Mohammad Insan (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
Nowadays, the importance of Corporate Social Responsibility (CSR) belongs not only to large companies but also to any organization. Along with the changing times and the development of today's technology, we can see companies trying to accommodate digital technologies in communication in implementing CSR. The primary value of Corporate Social Responsibility (CSR) is the image or reputation of the company. Implementation of CSR by lia s. Associates to date have used Instagram social media to communicate about CSR. Digital technology easily communicates CSR to stakeholders and consumers through social media. This research uses quantitative methods with an associative approach, namely research that asks about the relationship between two or more variables. The theory of research used in this study is stimulus-response theory. This study's results significantly influence the effectiveness of CSR messages in forming the company's image. In this study, it was also seen that the message was produced and conveyed to the audience and stakeholders of lia s. Associates Branding & Design Agency is quite effective through Instagram content. The message of Corporate Social Responsibility (CSR) in lia s. Associates Branding & Design Agency can be said to be very good. By using and utilizing content visually and well-informed storytelling, many respondents in this study, could understand the intended message.